2011
DOI: 10.4061/2011/830541
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis of Osmium Electrocatalysts for the Oxygen Reduction Reaction in the Absence and Presence of Aqueous Methanol

Abstract: Osmium electrocatalysts for the oxygen reduction reaction (ORR) were prepared by microwave irradiation of Os 3 (CO) 12 at different experimental conditions. The materials obtained were structurally characterized by FT-IR, micro-Raman spectroscopy and X-ray diffraction. Their chemical compositions were obtained by EDS. The electrocatalytic properties for the oxygen reduction reaction were evaluated by rotating disk electrode measurements in 0.5 mol L −1 H 2 SO 4 , in the absence and presence of aqueous methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recently there has been an interest in synthesizing electrocatalysts for PMFCs using a microwave thermal treatment. For example, PtRu/Carbon nanocomposite as anode in a direct methanol fuel cell (DMFC) [14]; CoSe [15], Ru [16], Os [17] and CoFeRu [18] electrocatalysts for the ORR; and Ru for the HOR [19] have been reported, but the use of organic solvents as reaction media remains. On the other hand, Sandoval et al have reported the synthesis of CoFeRu electrocatalyst using an organic solvent [18] compared with H 2 O [20] as microwave absorbing media, and they found a better electrocatalytic behavior for the ORR when the material is synthesized using H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been an interest in synthesizing electrocatalysts for PMFCs using a microwave thermal treatment. For example, PtRu/Carbon nanocomposite as anode in a direct methanol fuel cell (DMFC) [14]; CoSe [15], Ru [16], Os [17] and CoFeRu [18] electrocatalysts for the ORR; and Ru for the HOR [19] have been reported, but the use of organic solvents as reaction media remains. On the other hand, Sandoval et al have reported the synthesis of CoFeRu electrocatalyst using an organic solvent [18] compared with H 2 O [20] as microwave absorbing media, and they found a better electrocatalytic behavior for the ORR when the material is synthesized using H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Figure 7 d shows the mass-corrected Tafel plots for the ORR in the absence and presence of methanol for the non-activated ink and in its absence for the activated one. Through analysis, electrokinetic parameters were obtained and are summarized in Table 5 in conjunction with the OCP values for the OsRu electrocatalyst and the parameters reported in the literature for the mono [ 30 , 31 ] and bimetallic materials [ 13 ]. It can be observed that the OCPs are quite near one another, being slightly higher for the new electrocatalyst with CV before ORR study.…”
Section: Resultsmentioning
confidence: 99%
“…use of Ni-Ir and Ni-Os bimetallic NP alloys for hydrogenation reactions [48], Os NPs for CO oxidation [49,50], and Os NP electro-catalysts for PEM fuel cells [51] and direct methanol fuel cells [52].…”
Section: Osmium (Os)mentioning
confidence: 99%